INTERNASLISASI PROFIL PELAJAR PANCASILA DALAM UPAYA PENGUATAN PENDIDIKAN KARAKTER DI LEMBAGA PENDIDIKAN - Andi Arba Octavia; Andri Winarto (Al-Rabwah, 2023)
In a heterogeneous society where people can live hand in hand, looking after each other and loving each other to live in harmony, a constructive learning effort is needed to build a common understanding and harmony about the internalization of the Pancasila profile. This article's research aims to describe and examine more deeply the extent to which the internalization of Pancasila student profiles forms the character of students in educational institutions to realize national education goals. This research uses a qualitative approach with descriptive methods. In this study, the data obtained were analyzed using data analysis through library research research methods. The results of this study indicate that the internalization of Pancasila student profiles is an effort to strengthen character education. (1) having faith, piety to God Almighty, and having a noble character are key elements, namely faith and Spirituality are applied as guides and sources of support for individuals when navigating life's challenges (2) Global diversity is the ability of students to love differences (3) Gotong royong is a practice working together as a team, working together voluntarily to make tasks or activities smoother, easier and lighter (4) Creativity is the capacity of students to produce something original, significant, practical and impactful. This capacity can be seen in the ability of students to come up with original ideas, works, and actions. (5) Critical reasoning is the ability to solve problems and process information (6) Independence refers to having self-awareness of responsibility for learning processes and outcomes. But besides that, the results of this study also show that there are still some obstacles and gaps in the journey process.